EVOLVING TRENDS AND FUTURE PROSPECTS OF ADR MONITORING AND REPORTING: A LITERATURE REVIEW - Amin, Aneela; Malik, Madeeha; Hussain, Azhar (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: Owing to the importance of safe use of medicines, adverse drug reaction (ADR) monitoring has become a fundamental component to be performed along with other health-care services. Pharmacist being drug experts are in good position to provide professional assistance for ADR management. The aim of this study is to summarize research findings from developed and developing countries as well as from Pakistan regarding evolving trends and future prospects of ADR monitoring and reporting by pharmacists. Methods: A total of 49 studies were reviewed regarding trends of ADR monitoring using different search engines including google scholar, pubmed and science direct. Results: The review highlighted that there is need to identify the barriers and gaps to further enhance the effectiveness of current ADR monitoring practices. Conclusion: Strong legislation is required in Pakistan to develop and implement an effective ADR monitoring program to reinforce the conception of effective pharmacovigilance system in Pakistan. Keywords: Adverse drug reactions, Reporting, Pharmacist, Pharmacovigilance, Pakistan.